Vashe pravo . Vashe pravo . Your Right . Ваше право - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Discussion of protection for the witnesses and victims of crimes. Featured in the program: Savitskii, Valerii Mikhailovich (Doctor of Juridical Sciences) Contributors: Moskal'kova, T.N. (Anchor) Обсуждение проблемы защиты свидетелей преступлений и потерпевших. В программе участвуют: Савицкий, Валерий Михайлович (Доктор юридических наук) Создатели: Москалькова, Т.Н. (Ведущий/Ведущая)